Effect of Undegraded Protein and Energy Level on Intake and Digestibility of Nutrient and Blood Metabolite in Dairy Cows - Widyobroto, BP; Budhi, SPS; Agus, Ali (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
An experiment was conducted to determine the effect of undegraded protein and energy level on intake and digestibility of nutrient and glucose and urea blood content in dairy cows. The benefit of the research was to inform about the utilization of undegraded protein and energy level to optimize nutrient utilization in dairy cattle. The experiment was conducted in 4 month in the Department of Animal Nutrition and Feed Science, Faculty of Animal Science Gadjah Mada University. The experiment used 4 female rumen fistulated dry cows (Friesian Holstein Crossbreed) of 3.0-3.5 years old and 350â400 kg body weight. The treatments of this experiment were T1: 20% of undegraded protein (UDP) and 70% energy from requirement; T2: 20% undegraded protein and 120% energy from requirement; T3: 30% undegraded protein and 70% energy from requirement; and T4: 30% undegraded protein and 120% energy from requirement with Latin square design.Â Variables observed were intake and digestibility of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), Acid detergent fiber (ADF),Â and glucose and urea blood content. Collected data were analyzed by analysis of variances, and further differences were tested by orthogonal contrast. Results of the research showed that the level of UDP in the rations did not affect DM, OM, CP intake, rumen degradable protein (RDP), NDF and ADF; however level of energy had significant affect on DM, OM, CP,Â RDP and ADF intake. The level of UDP resulted in non significant difference in DM; but significantly different on CP digestibility. Digestibility of DM and OM were significantly influenced by the level of energy, but it did not influence NDF and ADF digestibility. Cattle treated with the high energy rations had higher blood glucose concentration than cattle treated with the low energy rations. Blood urea in cattle fed low UDP rations was higher than cattle fed high UDP rations. (Animal Production 10(2): 96-101 (2008)Â Key Words: Undegraded protein, nitrogen, energy, blood metabolite